2011
DOI: 10.1002/cbic.201000716
|View full text |Cite
|
Sign up to set email alerts
|

IspG‐Catalyzed Positional Isotopic Exchange in Methylerythritol Cyclodiphosphate of the Deoxyxylulose Phosphate Pathway: Mechanistic Implications

Abstract: H218O under the bridge: Recently, the deoxyxylulose phosphate (DXP) pathway was discovered to be a second pathway supplying isoprenoid biosynthetic precursors. One of steps is an IspG‐catalyzed reductive deoxygenation of methylerythritol cyclodiphosphate (MEcPP) to 4‐hydroxyl‐3‐methyl‐2‐(E)‐1‐diphosphate (HMBPP). Using [2‐13C,18O]‐MEcPP, we detected the positional isotopic exchange for the bridging oxygen in MEcPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
7

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 29 publications
(33 reference statements)
0
20
0
7
Order By: Relevance
“…It is known that MEcPP itself is stable for weeks at room temperature and such a positional isotope exchange depends absolutely on the presence of holo-IspG. Since the positional isotope exchange experiment was conducted in the absence of reductants, this result not only provides evidence supporting the reversible C-O bond cleavage at the MEcPP ( 16 ) C 2 position, but also implies that the formation of a cation intermediate occurs prior to any redox-chemistry (69). How IspG facilitates the MEcPP ( 16 ) C 2 C-O bond cleavage remains to be addressed.…”
Section: Mechanistic Studies Of the Mep Pathway Enzymesmentioning
confidence: 88%
See 1 more Smart Citation
“…It is known that MEcPP itself is stable for weeks at room temperature and such a positional isotope exchange depends absolutely on the presence of holo-IspG. Since the positional isotope exchange experiment was conducted in the absence of reductants, this result not only provides evidence supporting the reversible C-O bond cleavage at the MEcPP ( 16 ) C 2 position, but also implies that the formation of a cation intermediate occurs prior to any redox-chemistry (69). How IspG facilitates the MEcPP ( 16 ) C 2 C-O bond cleavage remains to be addressed.…”
Section: Mechanistic Studies Of the Mep Pathway Enzymesmentioning
confidence: 88%
“…(55, 68). In the cation model, reduction of the cation intermediate ( 29 ) (69) leads to a radical intermediate ( 30 ), which undergoes dehydration to 31 through a C-O bond cleavage mechanism as in the case of radical mediated dehydration reactions (70). Coordination of the C 3 -OH group of MEcPP ( 16 ) to the [4Fe-4S] cluster may also facilitate the 30 → 31 transformation as in the case of aconitase (71).…”
Section: Mechanistic Studies Of the Mep Pathway Enzymesmentioning
confidence: 99%
“…Despite the availability of holo and substrate-bound crystal structures [6-8] as well as extensive spectroscopic data from electron paramagnetic resonance (EPR), and isotope labelling experiments [4, 14], the identity and lifetime of the IspG reaction intermediates has been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…instead suggested that IspG-catalysis might involve a carbocation intermediate ( 31 , Figure 3B) [43,44]. The observation of a positional isotope exchange for the MEcPP C 2 bridging oxygen provided evidence for a reversible cleavage at this position, which is consistent with the formation of a carbocation intermediate 31 [45]. Based on the characterization of paramagnetic species detected during IspG steady-state turnover, Oldfield and co-workers went on to suggest that IspG catalysis might also involve an organometallic intermediate (e.g., 34 ) downstream of the carbocation intermediate 31 [46].…”
Section: Mechanictic Studies On Ispg and Isphmentioning
confidence: 88%